Transplantation of mitochondria from human malignant tumor cells as a method of tumor growth formation in the lungs of laboratory animals - O. I. Kit; E. M. Frantsiyants; A. I. Shikhlyarova; I. V. Neskubina (Исследования и практика в медицине)
Purpose of the study. Obtaining lung cancer tumors in Balb/c Nude mice by transplantation of mitochondria isolated from human malignant tumors.Materials and methods. Human lung cancer mitochondria were isolated using differential centrifugation on a high-speed refrigerated centrifuge. Mitochondrial samples were diluted with 0.9 % NaCl solution to a protein concentration of 3 mg per animal. Freshly isolated lung cancer mitochondria were once transplanted into the tail vein of male Balb/c Nude mice (n = 6) at the rate of 3 mg of protein per 1 animal in 0.4 ml of saline. Male mice of Balb/c Nude line (n = 4), which were injected with 0.4 ml of physiological solution into the tail vein once a day, served as a control group. All animals were killed by guillotine decapitation 4 months after intravenous transplantation of mitochondria isolated from lung cancer.Results. After the introduction of mitochondria into the tail vein of mice, no changes were found in the animals’ behavior, coloration of coverings. No respiratory problems, and no allergic reactions to the introduction of foreign protein were detected. Respiratory problems in mice with mitochondrial transplantation occurred between days 113 and 123, when a drop in body weight ≥ 25 % was observed. A uniform formation of tumor nodes together with an active filling of the lung space with blood was clearly visible on lung preparations of a Balb/c Nude male mouse after intravenous transplantation of mitochondria from the lung of a patient with non-keratinizing squamous cell carcinoma. Similar characteristics of tumor growth in the lung parenchyma of the patient and Balb/c Nude mice as direct recipients of tumor mitochondria involved solid structures consisting of fields, cells and strands of tightly fitting atypical polymorphic cells of the squamous epithelium with poorly developed cytoplasm. In addition, signs of adenocarcinoma included glandular and papillary-like structures and cell complexes with large nucleoli. Squamous epithelial cells were characterized by severe atypia and polymorphism. The shape of the nuclei was irregular in most cells, with large sizes, the color was heterogeneous, and the nucleoli were enlarged. Multinucleated cells, as well as pathological mitoses with clearly marked division figures, which testified to their proliferative activity, were encountered with a rather high frequency.Conclusions. Application of intravenous transplantation of mitochondria isolated from malignant human lung tumor in male mice of Balb/c Nude line causes growth and development of malignant foci in male Balb/c Nude mice. This is previously unknown fact in experimental oncology, allowing the study of new properties of mitochondria of human cancer cells.